(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Punica granatum seed oil, also known as pomegranate seed oil, is a valuable natural resource extracted from the seeds of the pomegranate tree (Punica granatum). The pomegranate is a fruit renowned for its antioxidant and beneficial properties, which extends to its seeds as well. Pomegranate seed oil has long captured the attention of researchers and manufacturers of cosmetic and medical products due to its remarkable characteristics and potential health benefits. The key significance of pomegranate seed oil lies in its unique composition, including a high content of fatty acids, antioxidants, vitamins, and bioactive compounds. This rich composition imparts numerous positive attributes to the oil, including antioxidant and anti-inflammatory characteristics, the ability to moisturize and improve skin conditions, as well as potential medical applications. In this review, we will explore the composition and properties of pomegranate seed oil, as well as research related to its effectiveness in cosmetic and medical applications. We will also discuss the potential limitations and challenges associated with the use of pomegranate seed oil, along with its role in the beauty and health market. This review aims to underscore the importance of pomegranate seed oil as a natural resource capable of enriching our lives and enhancing the condition of our skin and overall well-being.